Brazilian Companies And The Millennium Development Goals: Does The Global Compact Make A Difference? - Grigore, Alina (2011)
The Global Compact is the world’s largest corporate citizenship initiative, with over 7300 business participants and other stakeholders. Corporations sign the initiative whereby they voluntarily commit to align their business operations and strategy with ten universally accepted principles and catalyze actions in support of the broader UN Goals. The dissertation presents the results of an empirical study assessing whether or not the Global Compact helps Brazilian companies in achieving the Millennium Development Goals. Using a comparative case study approach, the study highlights the differences and similarities between two groups of companies: the Global Compact signatories and the non Global Compact supporters. The results, although inconclusive, show that the companies in the group of Global Compact signatories are more committed to the Millennium Development Goals than their counterparts. The study thus dismisses some of the criticism surrounding the Global Compact and shows that the initiative has no negative impact on companies’ performances in addressing the millennium goals.